School Choice and Quality - Daniele Checchi; Tullio Jappelli (Institute for the Study of Labor (IZA), 2003)
The 1993 Survey of Household Income and Wealth, a representative survey of the Italian population covering 24,000 individuals, reports detailed information on children attendance of public and private schools and parents? self-assessment of the quality of public schools in the city of residence. The survey also provides detailed information on the household demographic structure, income and parents? education. The empirical analysis indicates that the quality of schools is one of the driving factors in the choice between private and public schools. The results are robust with respect to the particular quality indicator used and the presence of provincial fixed effects.
Keywords: I21; I22; 330; private school; school quality; education finance; Privatschule; Allgemeinbildende Schule; Dienstleistungsqualität; Bildungsverhalten; Meinung; Schätzung; Italien